PENGARUH DEBT RATIO, DIVIDEN PAY OUT RATIO, RETURN ON EQUITY, PERUMBUHAN LABA, UKURAN KORPORASI, DAN PERPUTARAN KAS OPERASI TERHADAP PER (Studi Di Korporasi Sektor Manufaktur yang Listing di Bursa Efek Indonesia Jangka Waktu 2009 – 2012) - Herlambang Herlambang (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2019)
The mean of this research is examine  influence  debt ratio, dividend payout ratio variable, return on equity variable, earnings growth, size, and operating cash flow on price earning ratio (PER) in finance and manufacturing companies in Indonesia Stock Exchange in the period of year 2009 to 2012. The population in this study is the company in the sector manufacturing listed on the Indonesia Stock Exchange period of year 2009 to 2012. Samples were taken by purposive sampling and obtained 45 companies in the manufacturing sector as sample. Linear Regression Analysis with Simultaneous Significance Test (F statistic Test) and Individual Parameter Significance Test (Test Statistic t) is an analytical technique used in this study. The results showed that the independent variables of the debt ratio variable, size together significantly influence the price earnings ratio (PER) in the financial sector companies in the BEI and the independent variables of the dividend payout ratio and earnings growth together significantly influence  price earnings ratio (PER) at manufacturing companies listed on BEI. These results support data obtained from the World Bank regarding Indonesia's economic growth in 2012 on the production side, manufacturing performance is quite strong. This increase was achieved by the relatively large performance  domestic sectors such as those in processed foodstuffs, processed various beverages and processed various tobacco products (increasing 10.4% year on year) as well as fertilizer yields, yields from chemicals and rubber products (increased by 15.4% from year to year).